2013
DOI: 10.1097/iae.0b013e3182641848
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Posterior Segment Complications in Eyes Treated With the Boston Type I Keratoprosthesis

Abstract: Posterior segment complications occur in a significant percentage of patients after keratoprosthesis surgery, resulting in a persistent reduction of visual acuity in a significant proportion of the affected eyes (corrected distance visual acuity ≤ 20/400 in 61% with complications vs. 24% without complications at last follow-up). Given this, and the anatomic difficulties associated with management of posterior segment complications after keratoprosthesis implantation, it is of particular importance to prevent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
3
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 14 publications
0
73
3
3
Order By: Relevance
“…Goldman et al reported a significantly greater percentage of RDs in eyes undergoing Nd:YAG capsulotomy for RPM in their series. 19 This is in contradiction to a series by Chak and Aquavella, 13 which did not report any RD occurring in association with RPM formation or after Nd:YAG capsulotomy. We recommend that KPro patients with RPM formation and those that undergo YAG capsulotomies be followed closely in the immediate postoperative period for RD.…”
Section: Retroprosthetic Membrane And/or Nd:yag Capsulotomycontrasting
confidence: 52%
See 2 more Smart Citations
“…Goldman et al reported a significantly greater percentage of RDs in eyes undergoing Nd:YAG capsulotomy for RPM in their series. 19 This is in contradiction to a series by Chak and Aquavella, 13 which did not report any RD occurring in association with RPM formation or after Nd:YAG capsulotomy. We recommend that KPro patients with RPM formation and those that undergo YAG capsulotomies be followed closely in the immediate postoperative period for RD.…”
Section: Retroprosthetic Membrane And/or Nd:yag Capsulotomycontrasting
confidence: 52%
“…Our series is also the largest study investigating predisposing peri-and postoperative factors predisposing to RD after implantation. Compared with other series, 1,5,7,19,20 ours shows a much higher incidence of RD, most likely because of the relatively large number of patients with longer follow-up and the higher incidence of autoimmune cases.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Poor VA outcomes were confirmed after most posterior segment complications, such as retinal detachment, non-infectious vitreitis, central artery occlusion and retinal necrosis, as reported by Goldman et al [18]. Only 1 case with choroidal detachment and vitreous haemorrhage had good VA outcome.…”
Section: Discussionmentioning
confidence: 49%
“…Using the same VA criterion (0.05), Verdejo-Gomez et al [16] found a success rate of 83% (n = 12). Using 0.10 VA, but with different follow-up times, Greiner et al [14 ]had success in 89% (n = 36 at 1 year), Bradley et al [4] in 77% (n = 30), Aldave et al [17] in 68% (n = 27 at 1 year), Goldman et al [18] in 63% (n = 107), Zerbe et al [12 ]in 57% (n = 141) and Patel et al [19] in 43% (n = 50) of cases. This shows that our VA success rate is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%